Agriculture MSMEs Sustainability Farmers Exchange Rates in Indonesia During the Covid-19 Pandemic and Farmer Empowerment Solutions - Supriatna, Jajang; Djumarno, Djumarno; Badawy Saluy, Ahmad; Kurniawan, Deden (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
In "Rencana Pembangunan Jangka Menengah Nasional 2015-2019," which is regarded as a vital monetary sector, one of Indonesia's national development goals is the agricultural sector. One indicator of the success of agricultural development is the degree of farmer welfare, typically determined by the Nilai Tukar Petani (NTP). By comparing the quantity of NTP in each subsector and the implementation of the farming engagement activities, this article compares the level of farmer welfare in two farming sub-sectors, specifically estate crops and horticultural crops. The secondary data from Badan Pusat Statistik (BPS) from 2015 to 2021 were divided into two periods before and during pandemic COVID 19 (2015–2019 and 2020–2021), and the descriptive data on the farmer involvement activities with the sample point at Belitung Island. The data were analyzed with SPSS version 25 through Eta correlation analysis. The investigation revealed that horticultural crops and the NTP estate changed, with the NTP of horticultural plants being the most stable. Meanwhile, the horticulture and NTP estate crops tended to decrease and become less stable during pandemic COVID 19. We concluded that the agriculture industry was sustainable, particularly SME horticultural and estate crops. For a sustainable farming option, we advise employing marginal land for short crops using organic compost and reusing agriculture waste for bioorganic fertilizer.